2015
DOI: 10.1016/j.actamat.2015.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the effects of free surfaces on void strengthening with dislocation dynamics

Abstract: a b s t r a c tVoid strengthening in crystalline materials refers to the increase in yield stress due to the impediment of dislocation motion by voids. Dislocation dynamics (DD) is a modeling method well suited to capture the physics, length scales, and time scales associated with void strengthening. However, previous DD simulation of dislocation-void interactions have been unable to accurately account for the strong image forces acting on the dislocation due to the void's free surface. In this article, we emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…(2) is known to overestimate the critical stress because of a number of significant simplifications in the model [20], which is also demonstrated in our simulations in that the critical stresses for an isolated pair of obstacles surprisingly agree with Eq. (2) which assumes an infinite array of obstacles.…”
Section: (D) Are the Continuum Models For Dislocation/obstacle Interasupporting
confidence: 75%
See 2 more Smart Citations
“…(2) is known to overestimate the critical stress because of a number of significant simplifications in the model [20], which is also demonstrated in our simulations in that the critical stresses for an isolated pair of obstacles surprisingly agree with Eq. (2) which assumes an infinite array of obstacles.…”
Section: (D) Are the Continuum Models For Dislocation/obstacle Interasupporting
confidence: 75%
“…In dislocation/precipitate interactions, Bacon et al [17] included three precipitates in one simulation supercell with PBCs to represent an infinite row. Crone et al [20] found that introducing additional voids beyond three doesn't show a significant influence on the critical depinning stress in dislocation/void interactions. Studies of a dislocation passing a random array of obstacles have been pursued using line tension models [21][22][23] and DD simulations [24].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Voids, frequently introduced during manufacturing, processing, or irradiation, play a significant role in mechanical properties of metals by altering the microstructure and influencing dislocation motion [1][2][3]. Dislocationvoid interactions are important mechanisms of the strain hardening in which a higher applied shear stress is required for dislocations to bypass even nmsized voids [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although a void is generally considered to be the activated location for dislocation nucleation that promotes the incipient plasticity, the obstacle strength of voids was defined by evaluating the critical stress for a dislocation to glide past an array of voids. 16 Coincidentally, the depinning stress of an edge dislocation from a void in copper was also evaluated by the molecular dynamics (MD) simulation, 17 which contains less artificial criteria or parameters in the modeling of dislocation activities. To perform a multiscale model-based simulation, the atomic-scale study is a key component for which there is a lack of understanding.…”
Section: Introductionmentioning
confidence: 99%